Analisis Terhadap Putusan Nomor. 472/PDT.G/2012/PA.SPG Mengenai Isbat Nikah Poligami - Imam Mawardi (MASADIR: Jurnal Hukum Islam, 2021)
Abstrak: The author concluded that the Sampang Religious Court judge granted the request for marriage in decision No. 472 / Pdt.G / 2012 / PA.Spg. due to the procedures and reasons put forward by the petitioners as well as the legal basis taken by the judge, namely articles 4 and 5 of Law No.1 of 1974. However, the reasons put forward by the petitioners are still not fulfilled in article 7 paragraph (3) (KHI) and the legal basis adopted by the judge has not been fulfilled in Article 4 section (1) of Law No.1 of 1974. Kata Kunci : Isbat Marriage, Polygamy, Religious Court.